Electromagnetic simulation of a 16‐channel head transceiver at 7 T using circuit‐spatial optimization. Issue 6 (3rd February 2021) - Li, Xin; Pan, Jullie W.; Avdievich, Nikolai I.; Hetherington, Hoby P.; Rispoli, Joseph V.
Abstract : Purpose: With increased interest in parallel transmission in ultrahigh‐field MRI, methods are needed to correctly calculate the S‐parameters and complex field maps of the parallel transmission coil. We present S‐parameters paired with spatial field optimization to fully simulate a double‐row 16‐element transceiver array for brain MRI at 7 T. Methods: We implemented a closed‐form equation of the coil S‐parameters and overall spatial B 1 + field. We minimized a cost function, consisting of coil S‐parameters and the B 1 + homogeneity in brain tissue, by optimizing transceiver components, including matching, decoupling circuits, and lumped capacitors. With this, we are able to compare the in silico results determined with and without B 1 + homogeneity weighting. Using the known voltage range from the host console, we reconstructed the B 1 + maps of the array and performed RF shimming with four realistic head models. Results: As performed with B 1 + homogeneity weighting, the optimized coil circuit components were highly consistent over the four heads, producing well‐tuned, matched, and decoupled coils. The mean peak forward powers and B 1 + statistics for the head models are consistent with in vivo human results ( N = 8). There are systematic differences in the transceiver components as optimized with or without B 1 + homogeneity weighting, resulting in an improvement of 28.4 ± 7.5% in B 1 + homogeneity with a small 1.9 ± 1.5% decline in power efficiency. Conclusion: This co‐simulation methodology accurately simulates the transceiver, predicting consistent S‐parameters, component values, and B 1 + field. The RF shimming of the calculated field maps match the in vivo performance.